Knowledge graph and data application:intelligent recommendation - Jing ZHOU; Ximin SUN; Xiaokun YU; Xinning BIAN (Dianxin kexue)
Knowledge graph technology is an emerging internet technology with good forward-looking and strong technological advancement,and has broad application prospects.Knowledge graph technology provides the ability to analyze problems from the “relationship” perspective.It can deeply mine data,transform natural language into computer language,and display the value of data to the greatest extent.It can serve intelligent search,intelligent recommendation,risk early warning,intelligent operation,intelligent customer service,public opinion monitoring,equipment early warning and other businesses,greatly improving the production efficiency of enterprises.The comprehensive clustering algorithm,SVD decomposition algorithm,commodity-based collaborative concerns recommendation algorithm,user-based collaborative concerns recommendation algorithm and commodity similarity algorithm were studied.Combined with recommendation strategy,an intelligent recommendation system based on knowledge graph data application was proposed.It proves the feasibility and deployability of the data application with knowledge graph as the basic tool,which can fully meet the user’s demand for information on the internet platform.